Association of soluble receptor for advanced glycation end-products (sRAGE) serum on COVID-19 severity: A cross-sectional study. (February 2022) - Saputra, Gusti Noor Ramadany; Yudhawati, Resti; Fitriah, Munawaroh
Abstract: Background: Coronavirus disease 2019 (COVID-19) is a new health problem discovered in 2019 thus requires biomarkers that can detect early tissue damage. Soluble receptor for advanced glycation end-products (sRAGE) is a biomarker that can be used to identify early lung damage. Objective: Analyzing the association of serum sRAGE on COVID-19 severity. Methods: This study employed a cross-sectional design with a consecutive sampling method. It was conducted from May 2020–October 2021. The number of participants in this study was 145 participants which were divided into 2 groups (non-severe = 47 and severe = 98). Association of sRAGE serum on COVID-19 severity was analyzed using the chi-square test, Fisher's exact test, independence t -test, Mann Withney test, and Spearman's rank test with p -value <0.05. Results: The results of blood analysis showed several blood components such as leukocytes (9896.51 ± 4949.64/μL; z  = 2.431; p  = 0.015), lymphocytes (13.55 ± 8.48%; z  = 2.256; p  = 0.024), neutrophils (78.91 ± 10.50%; z  = 2.464; p  = 0.014), procalcitonin (0.92 ± 3.22 ng/mL; z  = 3.323; p  = 0.001), CRP (8.59 ± 7.62 mg/L; z  = 2.114; p  = 0.034), D-dimer (4360.29 ± 7797.81 ng/mL; z  = 2.186; p  = 0.029), and fibrinogen (474.58 ± 168.90 mg/dL; t  = 0.383; p  = 0.703). There was a significant comparison in serum sRAGE values in the non-severe group (0.78 [0.63–1.00] ng/mL) and severe group (1.47 [0.97–2.25] ng/mL; r  = 7.154; p  <0.001). There was a significant association between serum sRAGE and COVID-19 severity ( r  = 0.598; p  <0.001). The cut-off value for serum sRAGE between the severe and non-severe groups was 0.985 ng/mL. This study obtained sensitivity of 73.5%, specificity of 74.5% OR 8.077 and AUC 0.868 95% CI. Conclusion: There is a significant association between serum sRAGE and COVID-19 severity and there is also a significant difference in serum sRAGE in the two groups. Highlights: Serum sRAGE can be used to identify COVID-19 severity. The level of serum sRAGE in each COVID-19 patient is different. The blood components of each COVID-19 severity are different.